T Cell-Derived Apoptotic Extracellular Vesicles Ameliorate Bone Loss via CD39 and CD73-Mediated ATP Hydrolysis - Yang X; Zhou Y; Zhou F; Bao L; Wang Z; Li Z; Ding F; Kuang H; Liu H; Tan S; Qiu X; Jing H; et al. (International Journal of Nanomedicine)
Xiaoshan Yang,1– 3,* Yang Zhou,2,3,* Fuxing Zhou,4,* Lili Bao,2,3 Zhengyan Wang,5 Zihan Li,2,3 Feng Ding,2,3 Huijuan Kuang,6,7 Huan Liu,8 Shenglong Tan,1 Xinyuan Qiu,1 Huan Jing,9 Shiyu Liu,2,3 Dandan Ma1 1Department of Endodontics, Stomatological Hospital, School of Stomatology, Southern Medical University, Guangzhou, 510280, People’s Republic of China; 2State Key Laboratory of Oral & Maxillofacial Reconstruction and Regeneration, National Clinical Research Center for Oral Diseases, Shaanxi Key Laboratory of Stomatology, Department of Oral Biology, School of Stomatology, The Fourth Military Medical University, Xi’an, 710032, People’s Republic of China; 3State Key Laboratory of Oral & Maxillofacial Reconstruction and Regeneration, National Clinical Research Center for Oral Diseases, Shaanxi International Joint Research Center for Oral Diseases, Center for Tissue Engineering, School of Stomatology, The Fourth Military Medical University, Xi’an, 710032, People’s Republic of China; 4Department of Gynecology and Obstetrics, Xijing Hospital, The Fourth Military Medical University, Xi’an, 710032, People’s Republic of China; 5Department of Orthodontics, School and Hospital of Stomatology, Cheeloo College of Medicine, Shandong University & Shandong Key Laboratory of Oral Tissue Regeneration & Shandong Engineering Research Center of Dental Materials and Oral Tissue Regeneration & Shandong Provincial Clinical Research Center for Oral Diseases, Jinan, 250012, People’s Republic of China; 6Department of Orthopaedics, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, 710061, People’s Republic of China; 7State Key Laboratory for Manufacturing System Engineering, Xi’an Jiaotong University, Xi’an, 710054, People’s Republic of China; 8Department of Otolaryngology Head and Neck Surgery, Peking University Third Hospital, Beijing, 100871, People’s Republic of China; 9Department of Endodontics, Guangdong Provincial High-level Clinical Key Specialty, Guangdong Province Engineering Research Center of Oral Disease Diagnosis and Treatment, Peking University Shenzhen Hospital, Shenzhen, 518036, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dandan Ma, Stomatological Hospital, Southern Medical University, S366 Jiangnan Boulevard, Guangzhou, Guangdong, 510280, People’s Republic of China, Tel +86-20-34152996, Email mdd@smu.edu.cn Shiyu Liu, School of Stomatology, The Fourth Military Medical University, No. 145, West Changle Road, Xi’an, Shaanxi, 710032, People’s Republic of China, Tel +86-29-84772645, Email liushiyu@vip.163.comBackground: Osteoporosis is a major public health concern characterized by decreased bone density. Among various therapeutic strategies, apoptotic extracellular vesicles (ApoEVs) have emerged as promising agents in tissue regeneration. Specifically, T cell-derived ApoEVs have shown substantial potential in facilitating bone regeneration. However, it remains unclear whether ApoEVs can promote bone mass recovery through enzymatic activity mediated by membrane surface molecules. Therefore, this study aimed to investigate whether T cell-derived ApoEVs could promote bone mass recovery in osteoporosis mice and reveal the underlying mechanisms.Methods: ApoEVs were isolated through sequential centrifugation, and their proteomic profiles were identified via mass spectrometry. Western blot and immunogold staining confirmed the enrichment of CD39 and CD73 on ApoEVs. The role of CD39 and CD73 in hydrolyzing adenosine triphosphate (ATP) to adenosine was evaluated by quantifying the levels of ATP and adenosine. Inhibitors of CD39 and CD73, and an A2BR antagonist were used to explore the molecular mechanism of ApoEVs in promoting bone regeneration.Results: ApoEVs significantly reduced bone loss and promote the osteogenic differentiation of BMMSCs in ovariectomy (OVX) mice. We observed increased levels of extracellular ATP and a decrease in CD39 and CD73, key enzymes in ATP-to-adenosine conversion in bone marrow of OVX mice. We found that ApoEVs are enriched with CD39 and CD73 on their membranes, which enable the hydrolysis of extracellular ATP to adenosine both in vitro and in vivo. The adenosine generated by ApoEVs inhibits the inflammatory response and promotes osteogenesis through A2BR and downstream PKA signaling.Conclusion: T cell-derived ApoEVs are enriched with CD39 and CD73, enabling them to hydrolyze extracellular ATP to adenosine, thereby promoting bone regeneration via A2BR and PKA signaling pathway. Our data underscore the substantive role of T cell-derived ApoEVs to treat osteoporosis, thus providing new ideas for the development of ApoEVs-based therapies in tissue regeneration. Keywords: T cell apoptosis, apoptotic extracellular vesicles, CD39, CD73, adenosine, bone regeneration